Crowdsourcing as a means of fundraising for juvenile dermatomyositis. Issue 3 (21st February 2022) - Goldman, Nathaniel; Kassamali, Bina; Shahriari, Neda; Lonowski, Sarah; Nwankwo, Christy; Tran, Amity; Vleugels, Ruth Ann; LaChance, Avery
Abstract: This study used the crowdsourcing platform GoFundMe to analyze the financial hardships associated with treatment of juvenile dermatomyositis. Uncovered medical expenses, travel costs, and loss of income were all commonly cited reasons for fundraising, demonstrating high out‐of‐pocket costs and significant economic hardship associated with this disease, even among families with health insurance.